Status quo institutions and the benefits of institutional deviations - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2016)
The purpose of this paper is to nuance the widely held view that well-functioning institutions are the ultimate prerequisite for innovation and entrepreneurship. This is done by putting the spotlight on the role that formal and informal institutions have in serving the economic status quo, conserving old habits and incumbent economic interests. Therefore, existing institutions often act as impediments to entrepreneurship and innovation. We argue that a common yet underappreciated source of institutional change arises when individuals deviate from the behavior stipulated by existing institutions. All types of deviations are certainly not beneficial, but when they take the form of innovations introduced by entrepreneurs, they can be a particularly powerful source of economic and institutional change. An institutional setup should strike a balance between the need for stability that protects people's expectations and flexibility and adaptability to innovations and the ensuing entrepreneurship.
Keywords: L50; M13; O31; 330; Regulation; Norms; Innovation; Entrepreneurship